Metasurface-enhanced multifunctional flag nanogenerator for efficient wind energy harvesting and environmental sensing - Dong, Liwei (2024)
Wind energy, as a widely distributed and renewable energy resource, plays a crucial role in promoting self-powered wireless sensor networks and wind speed sensing. However, current research predominantly focuses on specific application purposes, lacking comprehensive investigations into integrated solutions. In this paper, a metasurface-enhanced multifunctional flag-type triboelectric nanogenerator (FTENG) is introduced, which enables efficient wind energy harvesting as well as accurate wind speed sensing over a wide range of wind speeds via the synergistic effect of metasurface treatment on the flagpole and flexible flag fixation approach. The flexible fixation maximally utilizes the upstream wake of metasurface configurations, boosting the energy harvesting power density by up to 23 times. The metasurface-enhanced FTENG with careful optimization, striking a balance between energy harvesting and sensing capabilities, achieves a linearity of 0.992 over a wind speed range of 2.3–14.4 m/s and a peak power density of 250 mW/m2. Finally, the FTENG demonstrates its excellent abilities to light LEDs, power the wireless sensor node (WSN), and serve as a self-powered environmental sensor. This work opens up an impactful possibility for developing versatile self-powered electronics by employing metasurface-enhanced wind energy harvesting techniques.